The Cosmos in the Making: Humans, Gods and Animals in Early Greek Theogonies - ALMQVIST, OLAF HUGO (Trinity College Dublin. School of Histories & Humanities. Discipline of Classics, 2018)
This thesis focuses on three early Greek cosmological poems, Hesiod's Theogony, the Orphic Derveni Theogony, and Protagoras' myth from Plato's homonymous dialogue. All three are variations on the same mythical material and explorations of how mortals, animals and divine beings interact. Although these narratives explore the same mythic material they have very different ideas about how the cosmos works. Hesiod begins his Theogony with the challenging divinity, Chaos, and describes a world where gods and humans are entirely separate and communicate through sacrifice. The Orphic poem replaces chaos with order and rejects Hesiodic difference in favour of a world based on cosmic kinship. Protagoras offers yet another transformation and, marginalising the role of the gods, his cosmological account focuses on humanity's struggle to separate itself from its innate animality through cultural knowledge. Despite these major differences, the variety and complexity of these early Greek cosmological myths and their underlying assumptions is not always appreciated in modern scholarship. In this thesis, I argue that we must be prepared to take these cosmological differences seriously, even when they challenge our foundational assumptions about what a good cosmology should be.
APPROVED
Keywords: Greek poetry, Ancient Cosmologies, Kinship, Sacrifice, Descola, Hesiod, Orpheus, Protagoras